Innovative Strategies of Islamic Religious Education Teachers in Building a Creative and Characterized Generation - Alsya'bani, Ibnu Syakur; Safitri, Dita Nur; Purnomo, Halim (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2025)
In the era of globalization and technological advancement, Islamic Religious Education (PAI) learning faces challenges in creating a creative and characterful generation. This study analyzes the innovative strategies of PAI teachers who are alumni of the University of Muhammadiyah Yogyakarta in building a creative and characterized generation. A qualitative approach is used to explore learning methods that are interactive, collaborative, and based on Islamic values. The results of the study show that a combination of creative approaches, such as group discussions, project-based learning, and the integration of digital technology, is effective in increasing students’ understanding of Islamic teachings while forming positive characters. The support of educational institutions through learning facilities, teacher training, and innovative curricula such as the Pancasila Student Profile Strengthening Project (P5) is also an important factor. These findings emphasize the importance of technology-based learning innovation and a student-centered approach in creating learning that is relevant to the needs of the times, forming students with character, and supporting the success of PAI education in the modern era.